2014
DOI: 10.4137/vrt.s15422
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Associated Risk Factors of Hepatitis E Virus Infection in Plateau State, Nigeria

Abstract: A cross-sectional study in Nigeria was undertaken to determine the epidemiology, seroprevalence, and associated risk factors, of hepatitis E virus (HEV). A total of 462 subjects were used for the study, categorized into four groups: apparently healthy persons, pregnant women, HIV positive subjects, and animal handlers. Information was obtained from subjects using interviewer-administered questionnaire. Blood samples were collected and analyzed for HEV antibodies (IgG and IgM) using enzyme-linked immunosorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
72
21
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(115 citation statements)
references
References 83 publications
(143 reference statements)
20
72
21
2
Order By: Relevance
“…Our finding is in congruence with the rates of 0.9% reported in a study among different populations including apparently healthy individuals in Plateau state [28] but differs from 1.7% reported among ARV naïve and experienced HIV patients in Ibadan [29]. Though varied rates of HEV IgM have been reported in other endemic regions of the world among different populations [30][31][32].…”
Section: Discussionsupporting
confidence: 80%
“…Our finding is in congruence with the rates of 0.9% reported in a study among different populations including apparently healthy individuals in Plateau state [28] but differs from 1.7% reported among ARV naïve and experienced HIV patients in Ibadan [29]. Though varied rates of HEV IgM have been reported in other endemic regions of the world among different populations [30][31][32].…”
Section: Discussionsupporting
confidence: 80%
“…The finding might be attributed to increased exposure of males to contaminated water, contaminated food sources and respective sanitary conditions as compared to females [2]. This disagrees with the reports of Junaid et al [6], Ekanem et al [15] and Ofosu-Appiah et al [11] where higher prevalence was recorded among females as compared with males.…”
Section: Discussioncontrasting
confidence: 57%
“…This difference may be ascribed to difference in geographical location, From previous studies in Nigeria, the prevalence observed in this study is lower than a 5.5% prevalence recorded in Ogbomoso [1] among individuals infected with HIV, 8.3% prevalence observed in Ekiti [3], 31.1% in Plateau [6], 7.7% in Cross river [15]. The difference in the prevalence may be ascribed to differences in the sensitivity and specificity of the assay used in various studies, difference in study groups, socio-economic, cultural, hygienic and climatic conditions.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations